Holistic profiling of the venom from the Brazilian wandering spider Phoneutria nigriventer by combining high-throughput ion channel screens with venomics - Cardoso, F. C.; Walker, A. A.; King, G. F.; Gomez, M. V. (Frontiers in Molecular Biosciences, 2023)
Spider venoms are a unique source of bioactive peptides, many of which display remarkable biological stability and neuroactivity. Phoneutria nigriventer, often referred to as the Brazilian wandering spider, banana spider or “armed” spider, is endemic to South America and amongst the most dangerous venomous spiders in the world. There are 4,000 envenomation accidents with P. nigriventer each year in Brazil, which can lead to symptoms including priapism, hypertension, blurred vision, sweating, and vomiting. In addition to its clinical relevance, P. nigriventer venom contains peptides that provide therapeutic effects in a range of disease models. In this study, we explored the neuroactivity and molecular diversity of P. nigriventer venom using fractionation-guided high-throughput cellular assays coupled to proteomics and multi-pharmacology activity to broaden the knowledge about this venom and its therapeutic potential and provide a proof-of-concept for an investigative pipeline to study spider-venom derived neuroactive peptides. We coupled proteomics with ion channel assays using a neuroblastoma cell line to identify venom compounds that modulate the activity of voltage-gated sodium and calcium channels, as well as the nicotinic acetylcholine receptor. Our data revealed that P. nigriventer venom is highly complex compared to other neurotoxin-rich venoms and contains potent modulators of voltage-gated ion channels which were classified into four families of neuroactive peptides based on their activity and structures. In addition to the reported P. nigriventer neuroactive peptides, we identified at least 27 novel cysteine-rich venom peptides for which their activity and molecular target remains to be determined. Our findings provide a platform for studying the bioactivity of known and novel neuroactive components in the venom of P. nigriventer and other spiders and suggest that our discovery pipeline can be used to identify ion channel-targeting venom peptides with potential as pharmacological tools and to drug leads.